Evaluation of Acacia Mangium in Structural Size at Green Condition - Gaddafi, Ismaili; Badorul Hisham, Abu Bakar; Khairul Khuzaimah, Abdul Rahim (Universiti Malaysia Sarawak, 2011)
Acacia mangium is one of the most popular choices in the reforestation and rehabilitation of abandoned shifting cultivation areas dated back to the 70’s. This paper looks into the evaluation of mechanical strength and physical properties in structural size at green condition for Acacia mangium. The mechanical strength properties tests were referred to the modulus of rupture, modulus of elasticity and tensile strength. Meanwhile, physical properties determination referred to basic density and moisture content. At green condition, Acacia mangium had been identified under the strength group SG6. It was found that strength value of modulus of rupture was higher than the tensile strength value with 44% stronger in bending compared to in tension. At the structural size, the mean value for moisture content and basic density at green condition were reported with 73.03% and 0.54g/cm3 respectively.